Anticancer-immune response towards breast cancer cell lines MDA-MB-231 and teratogenic assessment of Pereskia bleo leaves - Dalfi, Taif Kareem Khalaf (2024)
Conventional treatment for breast cancer, especially radiation and chemotherapy, have significant adverse effects on patients. Thus, an increased global focus on finding nontoxic and cytoselective treatments has emerged, which includes the study on herbs. Various herbs showed excellent bioactivities; however, there are herbs that can be toxic and teratogenic at certain dosage. The current study was conducted to assess the anti-cancer properties of P. bleo leaves in terms of their ability to induce apoptosis and to determine its anti-cancer-immune response by stimulating Natural Killer (NK) cells’ cytotoxicity against MDA-MB-231 breast cancer cells, as well as to evaluate its toxicity and teratogenicity in the animal model. Hexane, ethyl acetate and methanolic extracts of P. bleo leaves were tested for their cytotoxicity against normal cells MCF-10A and MDA-MB-231 cell lines by MTT assay. Methanolic extract showed the best activities and was used for subsequent experiments. Annexin V/PI assay and flow cytometric analysis were used to measure the induction of apoptosis, cell cycle arrest, and apoptotic protein expression by methanolic extract of P. bleo leaves (MEPB). Enzyme-linked immunosorbent assay (ELISA) was utilised to measure the level of interferon-gamma (IFN-γ), interleukins (IL)-8, IL-10, IL-12, IL-18, perforin, and granzyme B in healthy blood donors to determine the best concentration of MEPB leaves for activating NK cells. Flow cytometry and trypan Blue were used to measure NK cell counts and purity for subsequent experiments. Flow cytometric analysis and ELISA were used to determine the ability of MEPB to enhance NK cell cytotoxicity against MDA-MB-231 cells. The toxicity and teratogenicity of MEPB leaves were evaluated by observing the oestrous cycle, body weight, general behaviour and clinical signs, histopathological analyses, absolute body weights of dam’s visceral organs, and pregnancy outcomes, including the numbers of corpora lutea and implantation sites, pre- and post-implantation death (%), gravid uterine weight, number of live and dead foetuses, foetal body weight, sex ratio, and gross examination of the foetuses. The study used 40 female rats and was divided into 10 rat-control groups (distilled water) and 30 rat-MEPB groups (250, 500, and 1000 mg/kg/day). The MTT assay showed moderate cytotoxicity of MEPB leaves towards MDA-MB-231 breast cancer cells with an IC50 value of 64.57μg/mL. The flow cytometry data indicated that MEPB can arrest the cell cycle at the G0/G1 phase and stimulate apoptosis in MDA-MB-231 cells, increasing the Bax, p53, and caspase-3 while decreasing Bcl-2 expression. The results indicated that MEPB leaves could upregulate IFN-γ, IL-12, IL-18, perforin, and granzyme B levels and downregulate IL-8 and IL-10 levels in healthy blood. Breast cancer patients were found to have fewer NK cells than healthy donors, and approximately 87.09% of NK cells were effectively isolated. MEPB enhanced NK cells to kill MDA-MB-231 cells via apoptosis by upregulating perforin, granzyme B, and IFN-γ in healthy and breast cancer patient donors. The study also showed that the rat groups treated with various doses of MEPB leaves did not affect toxicity parameters, pregnancy outcomes, and foetotoxicity parameters. Our findings concluded that MEPB leaves induced apoptosis in MDA-MB-231 cells, with a significant capacity to regulate cytokines and increase NK cell cytotoxicity towards cancer cells without any evidence of toxicity and teratogenicity in rat-MEPB groups.